Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1088/0022-3700/9/14/020
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational excitation of polar molecules by electron impact. I. Threshold resonance in HF and HCl

Abstract: Differential scattering experiments with the crossed-beam method have been performed to study vibrational excitation of HF and HCl by electron impact at very low collision energies. The excitation functions for nu =1 and nu =2 have been measured from threshold to some eV above. In each case, an unusually strong and sharp threshold peak is observed with a broad resonance region following thereafter. The absolute cross sections reach values of the order of 10-15 cm2 for the threshold peaks in the nu =1 channel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
49
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(59 citation statements)
references
References 47 publications
8
49
2
Order By: Relevance
“…The most interesting feature in hydrogen halides is the existence of pronounced threshold peaks in the VE cross sections observed first by Rohr and Linder [1,2]. The cross sections in the threshold region attain very high values and represent the highest vibrationally inelastic cross sections measured.…”
Section: Introductionmentioning
confidence: 75%
“…The most interesting feature in hydrogen halides is the existence of pronounced threshold peaks in the VE cross sections observed first by Rohr and Linder [1,2]. The cross sections in the threshold region attain very high values and represent the highest vibrationally inelastic cross sections measured.…”
Section: Introductionmentioning
confidence: 75%
“…Interest in electron-HCl collisions was initiated by the discovery by Rohr and Linder [1] of sharp peaks at threshold in the cross sections for excitation of the v = 1 and v = 2 vibrational levels. These peaks attained surprisingly large absolute values and showed nearly isotropic angular distributions.…”
Section: Introductionmentioning
confidence: 99%
“…21 While information about photoelectron angular distribution (PAD) of CH 3 COO• is lacking, ab inito calculations indicated that the symmetry of the ground state of CH 3 COO• is different from that for HCOO•, that is, the ground state of CH 3 COO• is 2 A ′′ (B 2 ), with a 2 A ′ (A ′ ) lowlying excited state ∼0.1-0.2 eV higher in energy. 7 Molecules with sufficient dipole moments can bind an electron [22][23][24][25] and form dipole-bound anions. [26][27][28][29] Resonances observed in photodetachment experiments provided the first evidence for excited dipole-bound states (DBSs) near detachment thresholds of anions.…”
mentioning
confidence: 99%